Effect of tillage and precision nutrient placement on enhanced yield, productivity and profitability of maize (Zea mays) - SONNAD, PRAKASH; SINGH, TEEKAM; SINGH, RAJ; KAUR, RAMANJIT; KUSHWAHA, H L; G D, SANKETH; DAS, TANMAY; JAMAKHANDI, HUCHCHAPPA (The Indian Journal of Agricultural Sciences, 2025)
Minimum tillage led to improved growth and yield attributes, resulting in significantly higher grain and straw yields compared to conventional tillage, while being statistically similar to zero tillage. Band placement of 100% recommended dose of fertilizer (RDF) significantly higher yield attributes, productivity, and profitability of maize compared to band placement of 75% RDF and conventional 100% RDF, though it was statistically similar to point placement of 50% RDF. Band placement of 100% RDF led to markedly superior net returns and B:C ratio over 75% RDF applied through band placement and conventional 100% RDF, but showed no significant difference when compared with 50% RDF applied through point placement. Minimum tillage and zero tillage practices demonstrated clear economic superiority over conventional tillage, as evidenced by significantly greater net returns and improved benefit-cost (B:C) ratios, highlighting their potential for cost-effective and sustainable maize production Therefore, adopting point placement of 50% RDF and 75% RDF band placement can save 50% and 25% of fertilizers, respectively, compared to conventional 100% RDF broadcasting.